Generation and stability of cement soap films. Issue 9 (25th January 2021) - Ahmed Abdourahman, Djilani; Geniere, Arthur; Auriol, Mélodie; Dalas, Florent; Biance, Anne-Laure; Le Merrer, Marie
Abstract : By withdrawing a frame from a fresh cement suspension at controlled velocity, we find an optimum solid fraction to achieve both generation and stability of the cement soap films. Abstract : Foaming a cementitious suspension is a complex process that involves many multiscale chemical, physical and dynamical mechanisms. As a first step, we investigate here experimentally the possibility of withdrawing a single liquid soap film from a suspension of cement. We then determine the film lifetime and if particles are entrained or not. We vary the cement concentration, grain size, rheological properties and withdrawing velocity. We observed that the rheology of the cement paste, characterized through its yield stress, plays a key role in the film formation. We show that an optimum exists, as a low yield stress promotes film creation but is detrimental to the film stability. Another key result is that the rheology alone is not enough to describe film formation: the particle size in the suspension is also crucial, with large particles promoting film creation. Finally, we found that the withdrawing velocity also affects the ability to create films and the possibility to drag particles in them. Experiments performed with a silica suspension for comparison confirm these findings.